Cloning and expression of α-amylase in E. coli: genesis of a superior biocatalyst for substrate-specific MFC. Issue 4 (16th March 2019) - Nandy, Arpita; Jana, Samir; Khamrai, Moumita; Kumar, Vikash; Mukherjee, Shritama; Bhattacharyya, Arindam; Kundu, Patit P.
ABSTRACT: One of the most practical approaches for establishing a successful microbial fuel cell (MFC) is to fasten the oxidation rate of the substrate by the microorganisms to get quick paced electron transfer between microbes and electrode. A genetically modified Escherichiacoli, overexpressing α-amylase, is constructed and applied as biocatalyst in MFC using starch as substrate. The results are compared with nonrecombinant, native E.coli . The results show better performance for the MFC containing the recombinant strain demonstrated by higher power density (PD), lower resistance, and significant electrochemical activity. Maximum PD has been recorded as 279.04 mW m −2 compared to 120.33 Mw m −2 for the MFC operated with nonrecombinant E.coli . The impedance results also suggest the effectiveness of the recombinant strain by lowering the internal resistance by more than half order as compared to the nonrecombinant one. These results affirm that the engineered strain can be used as a superior biocatalyst in contrast to the native strain and by using the technique of genetic alteration; gene of interest can be inserted based on the substrate to be treated. So, this work gives a useful insight for accomplishing successful MFC operation with the use of bacterial stains engineered at the molecular level. Graphical Abstract: